"Prostate cancer is far more hidden…": Perceptions of stigma, social isolation and help‐seeking among men with prostate cancer. (7th November 2017) - Ettridge, K.A.; Bowden, J.A.; Chambers, S.K.; Smith, D.P.; Murphy, M.; Evans, S.M.; Roder, D.; Miller, C.L.
Abstract : The purpose of this study was to provide in‐depth insight into men's experiences of prostate cancer, specifically: perceived stigma and self‐blame, social isolation, unmet need and help‐seeking. A qualitative descriptive approach was used. Semi‐structured interviews were undertaken with 20 men diagnosed with prostate cancer, and thematic analysis was undertaken. Some participants perceived a stigma associated with prostate cancer and cancer in general, which sometimes acted as a barrier to disclosure. Self‐blame and internalisation of cause was not a prominent issue. Participants' descriptions of emotional distress, social isolation and anxiety demonstrated the impact of prostate cancer. Social isolation was most commonly reported as a physical consequence of treatment and/or side effects. Participants felt both support and ongoing care were limited at post‐treatment. Most did not seek or receive help for emotional or psychosocial problems from a formal source due to anticipated awkwardness, autonomous coping, not burdening others, unwanted sympathy and retaining privacy. Prostate cancer can cause considerable emotional and social burden for some men, and many are unlikely to seek or receive help. Men, and their support networks, require active encouragement throughout diagnosis, treatment and follow‐up to overcome barriers and access additional support, particularly for sexual, emotional and psychosocial issues.